WE NEED A BIGGER BOMB: A COMMUNITY ATTEMPT ON FIGHTING DENGUE FEVER IN A SUBURBAN SURABAYA, INDONESIA - Asri Asri; Khanitta Nuntaboot (UNEJ e-Proceeding)
Dengue had became a major public health problemin Southeast Asia, which seem to be seriouslygrowing in the future. Outbreaks were happened in2013, several evidences suggest that it were widelyunrecognized, much has been unreported and theamount of budget often not enough for running theeradication program.1Surabaya and Jakarta were two areas first reportedoutbreak of dengue fever in 1968. The following yearthis disease became epidemic which appearsannually with the outbreak pattern occurred everyfive or ten years. 2Based on East Java Province Health Department, inthe beginning of 2015 have been reported 1,817cases of dengue fever. This case increased by 85.4%from the previous year in the same month, i.e.January 2014, which only reached 973 cases. 3The concept of social capital widely addresseddirectly relates to the role and function ofcommunity health in providing health promotionwhich stressed the significance of participation,community capacity building, achieving thecommunity health promotion by collective actionand empowerment.4 Putnam and other scholarexplain that participation was very important in avariety of networks and see that social capital canhelp their collective action to achieve the goal ofgood health through the paths of individual socialcapital and social capital as a collective attribute. 5, 6,7According to the initial assessment at Tegalan, therewould be three level of dengue prevention andcontrol problem, which are at individual level,neighbourhood and community level, and intersectorallevel. These three level later on revealdifferent aspect of dengue management situation.This study tries to describe the existence ofcommunity social capital regarding dengue feverprevention and control in Tegalan sub-district,Surabaya.